Molluscan assemblages associated with Gigartina beds in the Strait of Magellan and the South Shetland Islands (Antarctica): a comparison of composition and abundance - Rosenfeld, Sebastián; Aldea, Cristian; Ojeda, Jaime; Marambio, Johanna; Hüne, Mathias; Troncoso, Jesús S; Mansilla, Andrés (Polar Research, 2017)
In this paper we evaluated the composition and abundance of molluscs associated with beds of the red algae Gigartina, located in the South Shetland Islands (Antarctic Peninsula) and the Strait of Magellan (southern Chile). During the summer season of 2013, samples were obtained by scuba diving using a 0.25 m2 quadrat, arranged randomly within the bed. We extracted a total of 15 quadrats per sampling site. For Antarctic Peninsula beds the most abundant species were the bivalve Lissarca miliaris (233 individuals) and the gastropod Laevilacunaria antarctica (94 individuals), while for Strait of Magellan beds the most abundant species was the polyplacophoran Callochiton puniceus (36 individuals). Comparative analysis between the two molluscan assemblages showed significant differences in the faunal composition between the Antarctic Peninsula and Strait of Magellan (f = 64.474; p = 0.0001). Therefore, molluscs reported in both areas are characteristic of their respective biogeographic area. Finally, Gigartina species play an important role in the formation of patterns of abundance and diversity of the communities associated with them.
Keywords: Sørishavet; alger; biodiversitet; biogeokjemi; bløtdyr; havbunnen; muslinger; snegler

Observations of energetic turbulence on the Weddell Sea continental slope - Fer, Ilker; Darelius, Elin; Daae, Kjersti B (Geophysical Research Letters, 2016)
Turbulence profile measurements made on the upper continental slope and shelf of the southeastern Weddell Sea reveal striking contrasts in dissipation and mixing rates between the two sites. The mean profiles of dissipation rates from the upper slope are 1–2 orders of magnitude greater than the profiles collected over the shelf in the entire water column. The difference increases toward the bottom where the dissipation rate of turbulent kinetic energy and the vertical eddy diffusivity on the slope exceed 10−7 W kg−1 and 10−2 m2 s−1, respectively. Elevated levels of turbulence on the slope are concentrated within a 100 m thick bottom layer, which is absent on the shelf. The upper slope is characterized by near-critical slopes and is in close proximity to the critical latitude for semidiurnal internal tides. Our observations suggest that the upper continental slope of the southern Weddell Sea is a generation site of semidiurnal internal tide, which is trapped along the slope along the critical latitude, and dissipates its energy in a 100 m thick layer near the bottom and within 10 km across the slope.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; havstrømmer; hydrografi; kontinentalsokkel

Local controls on sediment accumulation and distribution in a fjord in the West Antarctic Peninsula: implications for palaeoenvironmental interpretations - Munoz, Yuribia P.; Wellner, Julia S. (Polar Research, 2016)
We analyse surface sediment and its distribution in Flandres Bay, West Antarctic Peninsula, in order to understand modern day sediment dispersal patterns in a fjord with retreating, tidewater glaciers. The surface sediment descriptions of 41 cores are included in this study. The sediment facies described include muddy diatomaceous ooze, diatomaceous mud, pebbly mud, sandy mud and mud, with scattered pebbles present in most samples. In contrast to a traditional conceptual model of glacial sediment distribution in fjords, grain size in Flandres Bay generally coarsens from the inner to outer bay. The smallest grain size sediments were found in the bay head and are interpreted as fine-grained deposits resulting from meltwater plumes and sediment gravity flows occurring close to the glacier front. The middle of the bay is characterized by a high silt percentage, which correlates to diatom-rich sediments. Sediments in the outer bay have a high component of coarse material, which is interpreted as being the result of winnowing from currents moving from the Bellingshausen Sea into the Gerlache Strait. Palaeoenvironmental reconstructions of glacial environments often use grain size as an indicator of proximity to the ice margin. After a detailed analysis of a large number of cores collected in the study area, our findings highlight the variability in sedimentation patterns within a fjord and provide a valuable evidence of the complexity that may occur in the sedimentary record. Keywords: Flandres Bay; Antarctic Peninsula; sediment distribution; grain size.
Keywords: Antarktis; havbunnen; isbreer; miljøvitenskap; sedimenter; sedimentologi; topografi

The potential response of the hydrate reservoir in the South Shetland Margin, Antarctic Peninsula, to ocean warming over the 21st century - Marín-Moreno, Hector; Giustiniani, Michela; Tinivella, Umberta (Polar Research, 2015)
In the South Shetland Margin (SSM), Antarctic Peninsula, a bottom-simulating reflector indicates the presence of hydrate between ca. 500 and 3000 m water depth (mwd). The cold seabed temperatures allow hydrate stability at shallower water depths. During the past five decades, the Antarctic Peninsula has been warming up faster than any other part of the Southern Hemisphere, and long-term ocean warming could affect the stability of the SSM hydrate reservoir at shallow waters. Here, we model the transient response of the SSM hydrate reservoir between 375 and 450 mwd to ocean warming for the period 1958–2100. For the period 1958–2010, seabed temperatures are given by oceanographic measurements in the area, and for 2010–2100 by two temperature scenarios represented by the observed trends for the periods 1960–2010 (0.0034°C y−1) and 1980–2010 (0.023°C y−1). Our results show no hydrate-sourced methane emissions for an ocean warming rate at the seabed of 0.0034 °C y−1. For a rate of 0.023°C y−1, emissions start in 2028 at 375 mwd and extend to 442 mwd at an average rate of about 0.91 mwd y−1, releasing ca. 1.13×103 mol y−1 of methane per metre along the margin by 2100. These emissions originate from dissociation at the top of the hydrate layer, a physical process that steady-state modelling cannot represent. Our results are speculative on account of the lack of direct evidence of a shallow water hydrate reservoir, but they illustrate that the SSM is a key area to observe the effects of ocean warming-induced hydrate dissociation in the coming decades. Keywords: Hydrate; ocean warming; methane emissions; transient modelling; South Shetland Margin; Antarctic Peninsula.
Keywords: Sørishavet; geofysikk; havbunnen; havoppvarming; metanutslipp; oseanografi

Sessile macro-epibiotic community of solitary ascidians, ecosystem engineers in soft substrates of Potter Cove, Antarctica - Rimondino, Clara; Torre, Luciana; Sahade, Ricardo; Tatián, Marcos (Polar Research, 2015)
The muddy bottoms of inner Potter Cove, King George Island (Isla 25 de Mayo), South Shetlands, Antarctica, show a high density and richness of macrobenthic species, particularly ascidians. In other areas, ascidians have been reported to play the role of ecosystem engineers, as they support a significant number of epibionts, increasing benthic diversity. In this study, a total of 21 sessile macro-epibiotic taxa present on the ascidian species Corella antarctica Sluiter, 1905, Cnemidocarpa verrucosa (Lesson, 1830) and Molgula pedunculata Herdman, 1881 were identified, with Bryozoa being the most diverse. There were differences between the three ascidian species in terms of richness, percent cover and diversity of sessile macro-epibionts. The morphological characteristics of the tunic surface, the available area for colonization (and its relation with the age of the basibiont individuals) and the pH of the ascidian tunic seem to explain the observed differences. Recent environmental changes in the study area (increase of suspended particulate matter caused by glaciers retreat) have been related to observed shifts in the benthic community structure, negatively affecting the abundance and distribution of the studied ascidian species. Considering the diversity of sessile macro-epibionts found on these species, the impact of environmental shifts may be greater than that estimated so far. Keywords: Sessile macro-epibiont; ascidian; Antarctica; ecosystem- engineer.
Keywords: Sørishavet; bentiske organismer; biodiversitet; bryozoa; havbunnen; sekkdyr; økologi; økosystemer

Reproductive biology of the Antarctic ‘‘sea pen’’ Malacobelemnon daytoni (Octocorallia, Pennatulacea, Kophobelemnidae) - Servetto, Natalia; Torre, Luciana; Sahade, Ricardo (Polar Research, 2013)
The reproductive biology of the sea pen Malacobelemnon daytoni was studied at Potter Cove, South Shetland Islands, where it is one of the dominant species in shallow waters. Specimens collected at 15–22 m depth were examined by histological analysis. M. daytoni is gonochoristic and exhibited a sex ratio of 1:1. Oocyte sizes (>300 µm) and the absence of embryos or newly developed larvae in the colonies suggest that this species can have lecithotrophic larvae and experience external fertilization. This life strategy is in line with other members of the group and supports the hypothesis that this could be a phylogenetically fixed trait for pennatulids. It was observed that oocytes were generated by gastrodermic tissue and released to the longitudinal canal. Thereafter, they migrate along the canal until they reach maturity and are released by autozooids at the top of the colonies. This striking feature has not yet been reported for other pennatulaceans. Mature oocytes were observed from colonies of 15 mm in length, suggesting that sexual maturity can be reached rapidly. This is contrary to what is hypothesized for the vast majority of Antarctic benthic invertebrates, namely that rates of activities associated with development, reproduction and growth are almost universally very slow. This strategy may also explain the ecological success of M. daytoni in areas with high ice impact as in the shallow waters of Potter Cove.
Keywords: Sørishavet; bentos; havbunnen; marin biologi; nesledyr; reproduksjon

A consistent data set of Antarctic ice sheet topography, cavity geometry, and global bathymetry - Timmermann, Ralph; Le Brocq, Anne M; Deen, Tara J; Domack, Eugene W; Dutrieux, Pierre; Galton-Fenzi, Benjamin K; Hellmer, Hartmut H; Humbert, Angelika; Jansen, Daniela; Jenkins, Adrian; Lambrecht, Astrid; Makinson, Keith; et al. (Earth Syst. Sci. Data, 2010)
Sub-ice shelf circulation and freezing/melting rates in ocean general circulation models depend critically on an accurate and consistent representation of cavity geometry. Existing global or pan-Antarctic data sets have turned out to contain various inconsistencies and inaccuracies. The goal of this work is to compile in- dependent regional fields into a global data set. We use the S-2004 global 1-minute bathymetry as the backbone and add an improved version of the BEDMAP topography (ALBMAP bedrock topography) for an area that roughly coincides with the Antarctic continental shelf. The position of the merging line is individually chosen in different sectors in order to get the best out of each data set. High resolution gridded data for upper and lower ice surface topographies and cavity geometry of the Amery, Fimbul, Filchner-Ronne, Larsen C and George VI Ice Shelves, and for Pine Island Glacier are carefully merged into the ambient ice and ocean topographies. Multibeam survey data for bathymetry in the former Larsen B cavity and the southeastern Bellingshausen Sea have been obtained from the data centers of Alfred Wegener Institute (AWI), British Antarctic Survey (BAS) and Lamont-Doherty Earth Observatory (LDEO), gridded, and blended into the existing bathymetry map. The resulting global 1-minute topography data set (RTopo-1) contains maps for upper and lower ice surface heights, bedrock bathymetry, and consistent masks for open ocean, grounded ice, floating ice, and bare land surface.
Keywords: Antarktis; Sørishavet; batymetri; glasiologi; havbunnen; topografi

Measurements of ice thickness and seabed topography under the Fimbul Ice Shelf, Dronning Maud Land, Antarctica - Nøst, Ole Anders (Journal of Geophysical Research: Oceans, 2004)
This paper presents results from seismic measurements of the ice and water column thickness of the Fimbul Ice Shelf in the northeastern Weddell Sea. Seismic reflection measurements were conducted at 183 stations covering most of the ice shelf. Seismic velocities in the ice were derived from refraction measurements at 12 stations, distributed evenly across the area, as well as from temperature and density data from the Fimbul Ice Shelf. Velocities in the water were derived from temperature and salinity data from beneath the Fimbul Ice Shelf. Ice thicknesses were found to vary between 160 m and 550 m with uncertainties up to ±10 m. Water column thicknesses up to 900 m were found within the central ice shelf cavity, and values exceed 2000 m where the ice shelf overhangs the continental slope. Uncertainties in water column thickness are estimated to be ±60 m, and are dominated by the uncertainties in the shape of the seabed. Ice draft and seabed elevation was derived from ice and water column thickness assuming hydrostatic pressure. The resulting map of seabed elevation and water column thickness suggests that the strong westward flowing coastal current will be steered under the ice shelf and thus drive a sub-ice-shelf flow. Warm Deep Water does not have direct access to the ice shelf cavity, while relatively cold coastal waters shallower than 500 m will interact closely with the Fimbul Ice Shelf.
Keywords: Sørishavet; Weddellhavet; geofysikk; havbunnen; isshelf; oseanografi

Pilot shallow drilling on the continental shelf, Dronning Maud Land, Antarctica - Kristoffersen, Yngve; Strand, Kari; Vorren, Tore; Harwood, Dave; Webb, Peter (Antarctic Science, 2000)
A light, mining drill rig deployed from the stern of a research vessel has been used to carry out shallow drilling in 212 m water depth on the continental shelf in the eastern Weddell Sea. Penetration was 15 m below the seabed with 18% recovery in the 31 hours available for the experiment. The recovered glacigenic sediments are predominantly volcanic material of basaltic and andesitic composition with petrological characteristics and age similar to the continental flood basalts exposed in Vestfjella, about 130 km upstream from the drill site. The sediments include a reworked marine Miocene diatom flora. The material documents oscillations of the East Antarctic Ice Sheet over the past 30 ka. The lowermost diamicton probably represents a deformation till, and the grounding line retreated past the drill site 30 km from the shelf edge about 30 kyr BP. A readvance occurred during the Late Wisconsin Glacial Maximum. Assuming a reservoir correction of 1300 yr, marine conditions existed at the site between 10.1-7 kyr BP, and later at least between 2.8 and 2.5 kyr BP. The stratigraphy at the site has been disturbed by iceberg ploughing and/or contact between the ice shelf and the sea floor during local advances after 2.5 kyr BP.
Keywords: Dronning Maud Land; Weddellhavet; geokjemi; geologi; glasiologi; havbunnen; innlandsis; isshelf; kontinentalsokkel; stratigrafi

Glaciomarine turbidite and current controlled deposits in Prydz Bay, Antarctica - Kuvaas, Berit; Leitchenkov, German (Marine Geology, 1992)
A thick sequence (up to 2200 m) of presumed post late Eocene/early Oligocene glaciomarine sediments is inferred to be present on the Prydz Bay continental rise. In the absence of information from drillholes, we correlate to ODP Leg 119 drillsites on the shelf and compare with the seismic reflection pattern of glaciomarine sequences in the Weddell Sea. The inferred glaciomarine sediments in Prydz Bay appear to be deposited in a complex manner, suggesting interaction by both turbidity cur rents and strong bottom currents. Reflection seismic profiles from the lower continental slope and rise shows an abundance of current influenced deposits, such as sediment waves and large sediment ridges with similarities to contourite drifts. In addition, large channel-levee complexes are abundant, suggesting deposition by turbidity currents and other massflow processes. Large channels and sediment ridges trend oblique to the continental margin. The geometry and character of the seismic reflection pattern suggest that the ridges have been deposited under the combined influence of overflow from downslope channelized turbidity currents and strong bottom water flow. The observed sediment waves and the difference along eastern and western channel margins suggest that bottom currents are flowing towards the west. We suggest that the initiation of turbidite sedimentation occurred in the late Eocene-early Oligocene, when the Amery Ice Shelf reached the shelf edge for the first time. Onset of current controlled deposition may possibly be related to the opening of the Drake Passage at the Oligocene/Miocene boundary.
Keywords: Sørishavet; Weddellhavet; havbunnen; kontinentalmargin; marin geologi

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

Iceberg scouring and sea bed morphology on the eastern Weddell Sea shelf, Antarctica - Lien, Reidar; Solheim, Anders; Elverhøi, Anders; Rokoengen, Kare (Polar Research, 1989)
Keywords: Antarktis; glasiologi; havbunnen; isberg; isshelf; kontinentalsokkel; morfologi; seismologi

Aeromagnetic reconnaissance over the Riiser-Larsen Ice Shelf, east Antarctica - Kristoffersen, Yngve; Aalerud, Jan (Polar Research, 1988)
Keywords: Antarktis; glasiologi; havbunnen; isbreer; isfront; seismologi

Morphology of the Weddell Sea and southwest Indian Ocean - Johnson, G Leonard; Vanney, Jean-René; Elverhøi, Anders; LaBrecque, John L (Deutsche Hydrografische Zeitschrift, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; tektonikk

Model for submarine glacial deposition - Orheim, Olav; Elverhøi, Anders (Annals of Glaciology, 1981)
Keywords: Sørishavet; Weddellhavet; ekspedisjoner; forskning; geologi; havbunnen; oseanografi

Plough marks in the Weddell Sea - Orheim, Olav (Journal of Glaciology, 1979)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; forskning; havbunnen; oseanografi

Seismikk i Weddellhavet - Haugland, Kristen (Naturen, 1978)
Keywords: Sørishavet; ekspedisjoner; havbunnen; sedimentologi; seismologi

Om Antarktis, isfjell og havnivå - Maisey, George H (Naturen, 1978)
Keywords: NARE 1976/77; Sørishavet; ekspedisjoner; geologi; havbunnen; topografi

Antarktis og den internasjonale havbunnsorganisasjon - Traavik, Kim (Internasjonal politikk, 1974)
Keywords: Antarktis; Antarktistraktaten; havbunnen; havrett; internasjonal; politikk; ressurser; rett